The Effect Of The Combination Of Woolwich Massage And Selected Prayers Using Roll-On Saum Oil On Self-Efficacy And The Breastfeeding Process Of Primiparous - Ningsih, Dewi Andariya; , Liana Devi Oktavia; Kartika (International Journal of Public Health Excellence (IJPHE), 2025)
Constraints in breastfeeding are one of the reasons mothers can provide breast milk maximum. Doubt is generally experienced by mothers new to giving birth and breastfeeding for the first time. If the problem is not handled well, it will add to the amount of number failures in exclusive breastfeeding, which has an impact on the bad No, not only on the mother but also on the father and baby. Research This knowledge influence combination of Woolwich massage combined with prayer choice use roll-on Saum Oil connected with efficacy self and breastfeeding process. Research methods use quasi-experiments with use design. Two tests only designed. Variable X consists of massage, Wolwich, and prayer choice, as well as efficacy self, and variable Y, namely the breastfeeding process, using the Kolmogorov-Smirnov normality test with the Monte Carlo approach with control and intervention groups. Research results This shows that the number is 0.000 (<0.05), so there is influence in a way that is simultaneous or together between frequency massage, Wolwich, and self-efficacy towards the breastfeeding process. So that intervention massage, Wolwich, and prayer choice very much affect the breastfeeding process. The hope is to support positive, comprehensive, and related parties still done as much as possible. Possible for exclusive breastfeeding continuity.